Pharmacological Chaperones for β‐Galactosidase Related to GM1‐Gangliosidosis and Morquio B: Recent Advances. Issue 11 (23rd November 2021) - Stütz, Arnold E.; Thonhofer, Martin; Weber, Patrick; Wolfsgruber, Andreas; Wrodnigg, Tanja M.
Abstract: A short survey on selected β‐galactosidase inhibitors as potential pharmacological chaperones for GM1 ‐gangliosidosis and Morquio B associated mutants of human lysosomal β‐galactosidase is provided highlighting recent developments in this particular area of lysosomal storage disorders and orphan diseases. Abstract : Neurodegenerative GM1 ‐gangliosidosis and bone‐damaging Morquio B disease are caused by transportation‐challenged or catalytically incompetent β‐d ‐galactosidase mutants. For both lysosomal storage disorders there is currently no cure available. Great hope is focused on the concept of chaperone mediated therapy. Herein, we provide a short survey on selected iminosugar based β‐galactosidase inhibitors as potential pharmacological chaperones for GM1 ‐gangliosidosis and Morquio B associated mutants of human lysosomal β‐galactosidase highlighting recent developments in this particular area of lysosomal storage disorders and orphan diseases.